2002
DOI: 10.1128/aac.46.3.665-671.2002
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II and IV QuinoloneResistance-Determining Regions in Stenotrophomonas maltophilia Clinical Isolates with Different Levels of QuinoloneSusceptibility

Abstract: The quinolone resistance-determining regions (QRDRs) of topoisomerase II and IV genes from Stenotrophomonas maltophilia ATCC 13637 were sequenced and compared with the corresponding regions of 32 unrelated S. maltophilia clinical strains for which ciprofloxacin MICs ranged from 0.1 to 64 g/ml. GyrA (Leu-55 to Gln-155, Escherichia coli numbering), GyrB (Met-391 to Phe-513), ParC (Ile-34 to Arg-124), and ParE (Leu-396 to Leu-567) fragments from strain ATCC 13637 showed high degrees of identity to the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…Although mutations of the gyrA and parE genes at common sites were found in half of the drug-resistant strains, some previous publications have indicated that mutations at these sites are not related to the drug resistance of S. maltophilia Valdezate et al, 2002).…”
Section: Pmqr Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Although mutations of the gyrA and parE genes at common sites were found in half of the drug-resistant strains, some previous publications have indicated that mutations at these sites are not related to the drug resistance of S. maltophilia Valdezate et al, 2002).…”
Section: Pmqr Analysismentioning
confidence: 97%
“…Resistance to quinolones is mainly the result of chromosomally mediated mechanisms, including mutations in the targets of quinolones (DNA gyrase and topoisomerase IV) and decreased accumulation of quinolones (as a result of porin alteration or overexpression of efflux pump systems) Valdezate et al, 2002). It has also been found that quinolone resistance can be caused by plasmid-mediated quinolone resistance (PMQR) determinants, and the genes responsible for such resistance are named qnr .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to FQs in Gram-negative bacteria primarily results from point mutations in gyrA and/or parC gene sequences that render significantly lower drug affinity for DNA gyrase (containing mutated GyrA) and DNA topoisomerase (composed of mutated ParC) (1,57,65). In A. baumannii, the most common amino acid substitutions occur at position 83 of GyrA and position 80 of ParC (31,72,73,76).…”
Section: Discussionmentioning
confidence: 99%
“…A major mechanism of fluoroquinolone resistance in gramnegative bacteria involves changes in the structure (and hence in the affinity to the drugs) of the drug targets DNA gyrase (encoded by the gyrA and gyrB genes) and DNA topoisomerase IV (encoded by the parC and parE genes) (1,35,45). Specifically, amino acid substitutions at certain positions in subunits A (GyrA and ParC) of both DNA gyrase and DNA topoisomerase IV, due to point mutations in the QRDRs of the genes encoding these two polypeptides, have been found to contribute to fluoroquinolone resistance.…”
Section: Discussionmentioning
confidence: 99%